An Improved Sucker Rod Pumping System Model and Swabbing Parameters Optimized Design. (30th October 2018) - Li, Weicheng; Dong, Shimin; Sun, Xiurong
Abstract : Considering the impact of fluid flowing into pump on sucker rod pumping system (SRPS) dynamic behaviors, an improved SRPS model with new boundary model is presented, which is a fluid-solid coupled model with the interactions among surface transmission, rod string longitudinal vibration, plunger motion, and fluid flow. A uniform algorithm is adopted instead of the mixed iteration algorithm for the surface transmission and downhole rod string vibration submodels, to reduce the difficulties of solving the entire SRPS model. The dynamic response comparison is executed between the improved model and the current model, and the results show that it will bring a calculation error on pump load and pump fullness if the progress of fluid flowing into the pump (PFFP) is ignored. Based on this improved model, a multitarget optimization model is proposed and the dynamic behavior of SRPS is improved with the optimized swabbing parameters.